E-learning networked environments and architectures : a knowledge processing perspective - Pierre, Samuel (London : Springer, 2007)
Over the last decade researchers and practitioners have developed a wide range of knowledge related to e-learning. This book provides state-of-the-art e-learning networked environments and architectures carried out over the last few years from a knowledge management perspective. The book is organized into four parts: After an introductory chapter which attempts to characterize the e-learning environments, Part I exposes the problems of building knowledge scenarios followed by Part II which analyzes the process of building knowledge environments. Part III summarizes the principles, methods and issues related to the design of knowledge networks and finally Part IV addresses the problem of retrieving resources and knowledge from networked environments. Presenting a wide-ranging survey of methods and applications from contributors from around the world, this book will be a valuable resource for researchers, practitioners and graduates.
E-learning networked environments: concepts and issues -- PART I. BUILDING KNOWLEDGE SCENARIOS. -- Bridging the gap between E-learning modeling and delivery through the transformation of learnflows into workflows -- A toolkit for building geo-referenced lessons: design, implementation, and praxis -- PART II. BUILDING KNOWLEDGE ENVIRONMENTS. -- TELOS: a service-oriented framework to support learning and knowledge management -- Cognitive modeling of personalized software design styles: a case study in E-learning -- Skills superstore: online interactive study skills environment -- E-MEMORAe: a content-oriented environment for E-learning -- PART III. BUILDING KNOWLEDGE NETWORKS. -- Designing and testing an open-source learning management system for small-scale users -- Reinforcement agents for E-learning applications -- Secure communication layer for scalable networks of learning object repositories -- Quality of service and collaboration aspects in a distributed E-laboratory environment -- PART IV. RETRIEVING RESOURCES AND KNOWLEDGE. -- Quality rating and recommendation of learning objects -- Data mining in E-learning -- LORNAV: virtual reality tool for navigation of distributed learning objects repositories.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Distance education; Employees -- Training of -- Data processing; Internet in education; Knowledge management; Enseignement © distance; Gestion des connaissances; Internet en ©♭ducation.; Personnel -- Formation -- Informatique; Distance education; E-Learning; Employees -- Training of -- Data processing; Informatique; Internet in education; Knowledge management; Διαδίκτυο (Internet) στην εκπαίδευση.